Gut Microbiota and Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD): Emerging Pathogenic Mechanisms and Therapeutic Implications - Farah Abdelhameed; Attia Mustafa; Chris Kite; Lukasz Lagojda; Alexander Dallaway; Nwe Ni Than; Eva Kassi; Ioannis Kyrou; Harpal S. Randeva (Livers)
Non-alcoholic fatty liver disease (NAFLD), recently redefined as metabolic dysfunction-associated steatotic liver disease (MASLD), is the most common cause of chronic liver disease worldwide. Characterized by excessive hepatic fat accumulation, this disease encompasses a spectrum from simple steatosis to more severe forms, including steatohepatitis, fibrosis, and cirrhosis. Emerging evidence highlights the pivotal role of gut dysbiosis in the pathogenesis of MASLD. Dysbiosis disrupts the gut–liver axis, an intricate communication network that regulates metabolic, immune, and barrier functions. Alterations in gut microbiota composition, increased gut permeability, and translocation of pro-inflammatory metabolites/factors have been shown to trigger liver inflammatory and fibrotic cascades, exacerbating hepatic inflammation and injury. Recent studies have identified microbiome signatures associated with MASLD, offering promise as non-invasive diagnostic biomarkers and paving the way for new potential therapeutic strategies targeting gut dysbiosis. This review explores the crucial role of the gut microbiota in MASLD pathogenesis and highlights the need for further targeted research in this field to validate microbial biomarkers and optimize therapeutic strategies. Comprehensive understanding of the gut–liver axis may enable innovative diagnostic and therapeutic approaches, transforming the clinical management of MASLD.